Calcium binding and transport by coenzyme Q - Bogeski, Ivan; Gulaboski, Rubin; Kappl, Reinhard; Mirceski, Valentin; Stefova, Marina; Petreska, Jasmina; Hoth, Markus (American Chemical Society (ACS), 2011)
Coenzyme Q10 (CoQ10) is one of the essential components of the mitochondrial electron-transport chain (ETC) with the primary function to transfer electrons along and protons across the inner mitochondrial membrane (IMM). The concomitant proton gradient across the IMM is essential for the process of oxidative phosphorylation and consequently ATP production. Cytochrome P450 (CYP450) monoxygenase enzymes are known to induce structural changes in a variety of compounds and are expressed in the IMM. However, it is unknown if CYP450 interacts with CoQ10 and how such an interaction would affect mitochondrial function. Using voltammetry, UV-vis spectrometry, electron paramagnetic resonance (EPR), nuclear magnetic resonance (NMR), fluorescence microscopy and high performance liquid chromatography-mass spectrometry (HPLC-MS), we show that both CoQ10 and its analogue CoQ1, when exposed to CYP450 or alkaline media, undergo structural changes through a complex reaction pathway and form quinone structures with distinct properties. Hereby, one or both methoxy groups at positions 2 and 3 on the quinone ring are replaced by hydroxyl groups in a time-dependent manner. In comparison with the native forms, the electrochemically reduced forms of the new hydroxylated CoQs have higher antioxidative potential and are also now able to bind and transport Ca(2+) across artificial biomimetic membranes. Our results open new perspectives on the physiological importance of CoQ10 and its analogues, not only as electron and proton transporters, but also as potential regulators of mitochondrial Ca(2+) and redox homeostasis.